Layout Optimization of Construction Waste Recycling Facilities for Development of New Urban Areas from Centralized and Decentralized Processing Collaboration Perspective - Shen, Ling; Liu, Yang; Ge, Hongyan (KSCE Journal of Civil Engineering, 2023)
The generation, treatment and safe disposal of construction waste have become major problems in new urban areas of China. And the existing research has not been carried out based on the recycling characteristics of scattered, low efficiency and large negative externalities of construction waste processing in the development of new areas. This research studies the optimal location of construction waste centralized and decentralized processing facilities based on the characteristics of the generation end and the demand side of new urban areas. Firstly, grey relational analysis method is used to determine the location of centralized processing facilities. Then, a multi-objective integer programming model is built by comprehensively considering cost, side effect on society and carbon emissions during transportation, and the optimal location and dynamic adjustment of decentralized processing facilities are determined. Finally, taking the development of a new area in China as an example, the network of construction waste recycling facilities is established to verify the effectiveness of this model. The research results show that the layout strategy formulated with this method can maintain the dynamic optimal layout of the system from the perspective of the whole region, and realize the utilization of construction waste with low cost, low transport carbon emission and low social negative impact. The analysis method system established in this paper is universal, which can provide reference for the relevant government departments to plan the construction waste recycling facility network of the area, and provide guidance for the investment decisionmaking and operation management of related enterprises.